(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
` Boosting communicative competence in language learners involves various strategies and techniques tailored to develop their ability to effectively communicate in the target language. Generally speaking, today the communicative approach to language teaching refers to teaching students a number of skills which are aimed at developing their ability to communicate. These skills are based on more or less commonly agreed upon teaching principles which in practice can be applied in different ways, depending on the teaching context, the age and level of the learners, their learning goals, etc.